Impact of climate finance on gender equity for sustainable global development: Can aid for climate action also aid gender equity? - Waheed, Shariq; Waheed, Husnain (Brazilian Journal of Science, 2022)
The idea of climate action including adaptation and mitigation is preposterous and unattainable without financial backing and investments, a requisite, which is fulfilled by climate financing. However, the concept of climate action is not synonymous with climate justice, where tackling climate threats with the aid of climate finance does not always manifest in gender-equitable conditions. The current paper presents a broad review of literature, expanding on the ‘distributive, contextual, and procedural’ equity framework on climate mitigation and adaptation strategies including, coastal wetland protection and sustainable agroforestry. The review reveals that the implications of climate finance are not parallelly distributed between men and women and climate action, in several contexts and spaces, exacerbates already existing structural and climate change-induced inequalities even further. To optimize the effectiveness of climate finance, the paper urges authorities and policymakers to integrate gender-responsive components into climate finance frameworks to ratify structural and behavioral inequalities along with empowering women to engage in climate action ventures without undermining their adequate living conditions.